Milk yield, its composition and performance of Malpura ewes under protocol of grazing and supplementation - KARIM, S A; SANTRA, A; SHARMA, V K (The Indian Journal of Animal Sciences, 2014)
The reported study was conducted to assess potential milk yield of Malpura ewes under protocol of grazing withconcentrate supplementation @ 1.5% of body weight. The bio mass yield of Ceflchrlls ciliaris dominated pasture was18.2 q/ha and the mouth grab sample of the vegetation contained 8.3% CP while the concentrate mixture offered to the ewes had 15.7% CPo M ilk yield of the ewes was 525 ml on the date of lambing and peak yield was recorded on 1 sl ,2ndan 3rd week of lactation (548 ml) and the yield gradually declined by 12th week of lactation. Based on lactation recordsof 3 months, the daily milk yield of the ewes was 496 g/day. The average milk fat content of the ewes in total lactationlength of 90 days was 6. 1%: the milk fat content increased with decrease in milk yield (r =- 0.62). On an average the milkcontained 3.4% lactose, 5.1 % protein, 9.5% SNF and 15.8% TS. The ash content was higher in 1 st and 2nd week (3.3%)than other periods (0.9%). The ewes showed linear gain in body weight after termination of pregnancy in lactation phaseof the study. It is concluded that average milk yield of Malpura ewes was 496 g/day in the lactation period of 3 months.Further the lactating ewes showed linear gain in body weight under protocol of grazing with concentrate supplementation@ 1.5% body weight which was adequate for their requirements.